THE STATUS AND RIGHTS OF AN ILLEGITIMATE CHILD ACCORDING TO MAZHAB ASY-SYAFI'I PERSPECTIVE ON THE DEVELOPMENT OF ISLAMIC FAMILY LAW IN INDONESIA - Nur Shadiq Sandimula (Jurnal Ilmiah Al-Syir'ah, 2019)
The problem of free social interaction brings a grave danger to society which is involved the sexual act out of wedlock which is known as fornication (zina) and causes a harming impact on their offspring psychologically, socially and religiously in the society. This paper is trying to analyze the perspective of an order of Shafi'i on the statuses and the rights of an illegitimate child. Based on library research, this research used a descriptive analysis method to derive the data and information from primary classical textbooks of mazhab Shafi'i. The result of this research shows that according to mazhab Shafi'i, a child who was born under six months after intercourse with her legal husband is believed to be an illegitimate child of another man. The children are not related to his/her biological father and the status of the child for his / her father is an ajnabiyya (non-mahram). If the child is a girl, her biological father is fully permissible to marry her. In the conclusion, the child is not related to his / her biological father and does not have any rights from his/her biological father whether a right to receive household expenses, a guardianship for marriage, and rights of inheritance.